PTU-009 Are Publication Rates From Regional Meetings Comparable With Those From National Meetings?. (9th June 2014) - Burden, M; Mooney, PD; Bardhan, KD; Kurien, M; Sanders, DS
Abstract : Introduction: The pinnacle for SPRs who undertake research is to initially present in abstract form at national and international meetings and ultimately publish in peer-reviewed journals. We have previously shown that full publication rate from the BSG has ranged from 20.4–55.9%, furthermore the trend over a 15 year period suggests a reduction in full publication rates. There has been no study which assesses the publication rate or utility of regional research meetings in the UK. Our study prospectively presents 10 years of abstract publications rates and qualitative data from the South Yorkshire Regional Gastroenterology meeting (the Bardhan Fellowship). Methods: 112 abstracts were presented at the meeting between 2003 and 2012. Abstracts were ranked at each meeting by peer review and the winner awarded a monetary prize. Subsequent full publication rates were determined using Medline searches of peer-reviewed journals. Searches were made firstly by the author's name, subsidiary authors', keywords from the abstract titles and personal communication with presenters. Qualitative data collected at each meeting in the form of an evaluation form was also available to provide subjective feedback from attendees on the relevance of the event. Results: Overall, 37 (33%) abstracts went on to be published in peer-reviewed journals. Of the 112 abstracts presented, 32 were ranked in the top 3 of their respective meetings, of whom 24 went on to be published in peer-reviewed journals (75%), compared with 13 of the 80 not ranked (16.25%) (p < 0.0001). Ranking within the top 3 resulted in a higher impact factor (median 4.06) publication, compared with those ranked outside the top 3 (2.87) (p < 0.05), and to more rapid publication (12.8 vs. 19.3 months). Qualitative feedback indicated that >95% attendees felt the meeting was educationally beneficial, relevant to their professional development and had encouraged them to participate in research for themselves. Conclusion: This is the first study to assess the value of regional SPR meetings. In terms of overall abstract publication rate, the data shows that the Bardhan fellowship is comparable with the BSG. Peer review appears to reliably predict subsequent publication success. Trainees ranked 'top three' at the meeting are significantly more likely to publish their work in peer-reviewed journals. Regional meetings can promote research and are a 'friendly' environment in which SPR's can improve their presentation skills and may stimulate them to consider a formal period of research. We would encourage Deanery support for such initiatives. Disclosure of Interest: None Declared.